Body Image and Body Avoidance Nine Years After Bariatric Surgery and Conventional Weight Loss Treatment - Legenbauer, Tanja; Müller, Astrid; de Zwaan, Martina; Herpertz, Stephan (Frontiers in Psychiatry, 2020)
Recently, there has been an increasing focus on body image dissatisfaction (BID), both as a motivational factor for seeking bariatric surgery and as a factor influencing weight loss outcome after surgery. Although associations have been reported between BID, emotional distress and successful weight loss (SWL), conclusions are limited due to methodological issues such as non-weight-specific assessment tools for body image and neglect of behavioral components (e.g. body avoidance, BA). The present study seeks to report on BID and BA nine years after bariatric surgery using a cross-sectional data set from the 9-year follow-up assessment of the Essen-Bochum Obesity Treatment Study (EBOTS). In total, N = 291 participants of the original EBOTS sample were included in the present analyses (N = 78 bariatric surgery patients, SURG; N = 124 patients of a conventional treatment program, CONV; and N = 83 individuals with obesity not seeking treatment, OC). Current body image facets (BID and BA) were captured at the 9-year follow-up assessment via silhouette scales adapted for use in samples with obesity. Moreover, BID was assessed retrospectively to obtain baseline attitudes. Possible influences of eating disorder symptoms and depression/anxiety were controlled for and assessed via standardized self-report measures. The results imply an improvement in BID in the SURG group, but not in the CONV and OC groups. The level of BA in relation to clothing was significantly higher in the CONV group compared to both the SURG and OC group. Current BID as well as BA were positively associated with current body weight as well as depression, anxiety and levels of disinhibited eating. A positive change from baseline to current levels of BID was associated with successful weight loss, independently of treatment. The findings emphasize the role of the different components of body image after surgery for mental health features, and suggest a robust relationship between BID and weight loss (success). Thus, it might be helpful to address BID in treatment. However, further research, particularly in the form of prospective studies, is necessary to determine the direction of influence.